Move past adversity or bite through it?: diet quality, physical activity, and sedentary behavior in relation to resilience - Ruf, Alea; Ahrens, Kira F.; Gruber, Judith R.; Neumann, Rebecca J.; Kollmann, Bianca; Kalisch, Raffael; Lieb, Klaus; Tüscher, Oliver; Plichta, Michael M.; Nöthlings, Ute; Ebner-Priemer, Ulrich; Reif, Andreas; et al. (The American psychologist, 2025)
Adverse life experiences are associated with an increased risk of mental disorders. The successful adaptation to adversity and maintenance or quick restoration of mental health despite adversity is referred to as resilience. Identifying factors that promote resilience can contribute to the prevention of mental disorders. Lifestyle behaviors, increasingly recognized for their impact on mental health, are discussed as potential resilience factors. Several studies found that healthy eating and physical activity (PA) are positively associated with resilience. However, most of these studies assessed resilience through questionnaires, which is unsatisfactory given that resilience research is moving toward conceptualizing resilience as the outcome of a dynamic process, which can only be assessed prospectively and longitudinally. The present study is the first to assess the relationship between diet quality, PA, sedentary behavior (SB), and resilience, captured prospectively and longitudinally in a sample of 145 individuals (75.17% female; Mage = 28.88, SDage = 7.80; MBMI = 24.11, SDBMI = 3.97). Resilience was assessed as the relationship between stressor exposure and mental health (i.e., the stressor reactivity score: higher scores indicate lower resilience and vice versa). Diet quality (i.e., the Healthy Eating Index) was assessed on the basis of app-based food records and 24-hr dietary recalls. PA and SB were objectively recorded through accelerometers. Regression analysis showed that neither diet quality nor PA and SB predicted resilience (ps > .30). Profound differences in the conceptualization and operationalization of resilience might explain the contrary findings. Prospective longitudinal studies are needed to replicate the findings of the present study. (PsycInfo Database Record (c) 2025 APA, all rights reserved)